INTERACTION BETWEEN SYMPATHO-ADRENAL ACTIVITY AND IMMUNE MEDIATORS IN PATIENTS WITH METABOLIC SYNDROME - N. R. Uzbekova; M. A. Khuzhamberdiev; I. M. Tashtemirova (Российский кардиологический журнал, 2014)
Aim. To investigate the interactions between the functional status of sympathoadrenal system and immune meditators in patients with metabolic syndrome (MS).Material and methods. In total, 55 patients (age 35-57 years, mean age 46,7±2,1 years) were examined, including 30 individuals with MS. In all participants, the following parameters were assessed: carbohydrate metabolism parameters (fasting glucose and insulin), lipid metabolism parameters (total cholesterol (TCH), triglycerides, high-density lipoprotein CH (HDL-CH), and low-density lipoprotein CH (LDL-CH)), 24-hour urine excretion of free and conjugated catecholamines (CA), monoamine oxidase (MAO) activity, and cytokine status (interleukin-6 (IL-6), IL-10, and tumor necrosis factor а (TNF-а).Results. MS patients demonstrated a significant increase in all CA fractions, particularly noradrenaline (NA). The total NA levels were elevated, compared both to the levels of other bioactive amines and to the respective levels among controls and hypertensive patients. There was a positive correlation between 24-hour NA excretion and glycemic index (r=0,67, р<0,01), as well as between NA levels and body mass index (BMI) values (r=0,65, р<0,01). Moreover, there was a positive correlation between 24-hour NA excretion and blood pressure (BP) levels (r=0,62, р<0,01). The elevated 24-hour CA excretion was accompanied by a significant reduction in MAO levels across all study groups. There was a negative correlation between MAO and 24-hour NA excretion in MS patients (r= -0,68, р<0,01). These patients also had elevated levels of IL-6 and TNF-а. There was a positive correlation between IL-6 levels and the following parameters: elevated BP (r=0,67, р<0,01), BMI (r=0,59, р<0,01), TNF-а levels (r=0,53, р<0,01), and increased 24-hour NA excretion (r=0,65, р<0,01).Conclusion: Increased sympatho-adrenal activity disturbs humoral immune response, which is an important pathogenetic marker of MS progression. This emphasises the need for pathogenetically sound strategy of pharmacological treatment for these patients.